Objetivos de Desarrollo del Milenio: ¿se puede reducir el hambre a la mitad en el Perú? - Yamada, Gustavo; Basombrío, Leda (Universidad del Pacífico, 2008)
This paper assesses the feasibility of Peru achieving the first MDG with respect to the eradication of hunger: specifically, halving the deficit of calorie intake by the population of Peru. To evaluate this possibility, a panel model for the period 2001-2005 is estimated and its coefficients are used as inputs in order to run simulations up to the year 2015. The main conclusion of this analysis is that the achievement of the goal, based solely on economic variables such as income growth or its radical redistribution, is barely feasible. The simulation scenarios clearly reveal the multidimensional nature of the problem of calorie deficits. The most cost-effective scenario for halving hunger over the next ten years in Peru would involve a 7% annual growth rate for the economy, the achievement of the education and sanitation millennium goals, and the investment of 44 to 66 million dollars annually in extending the coverage of the school breakfast program to cover all poor children in the country.